Effect of three fatty acids from the leaf extract of Tiliacora triandra on P-glycoprotein function in multidrug-resistant A549RT-eto cell line - Kaewpiboon, Chutima (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Cancer cells have the ability to develop resistance to chemotherapy drugs, which then leads to a reduced effectiveness and success of the treatment. Multidrug resistance (MDR) involves the resistance in the same cell/tissue to a diverse range of drugs of different structures. One of the characteristics of MDR is an overexpression of P-glycoprotein (P-gp), which causes the efflux of the accumulated drug out of the cell. The MDR human non-small cell lung carcinoma cell line with a high P-gp expression level (A549RT-eto) was used to investigate the bioactive compounds capable of reversing the etoposide resistance in this cell line. MATERIALS AND METHODS: The leaves of Tiliacora triandra were sequentially extracted with hexane, dichloromethane, methanol and water. Only the hexane extract reduced the etoposide resistance of the A549RT-eto cell line, and was further fractionated by column chromatography using the TLC-pattern and the restoration of etoposide sensitivity as the selection criteria. RESULTS: The obtained active fraction (F22) was found by nuclear magnetic resonance and gas chromatography-mass spectroscopy analyses to be comprised of a 49.5:19.6:30.9 (w/w/w) mixture of hexadecanoic: octadecanoic acid: (Z)-6-octadecenoic acids. This stoichiometric mixture was recreated using pure fatty acids (MSFA) and gave a similar sensitization to etoposide and enhanced the relative rate of rhodamine-123 accumulation to a similar extent as F22, supporting the action via reducing P-gp activity. In contrast, the fatty acids alone did not show this effect. CONCLUSION: This is the first report of the biological activity from the leaves of T. triandra as a potential source of a novel chemosensitizer.